SEQUENCE APPLICATION OF BRAIN MRI WITH ORTHODONTIC BRACKET - Aryadiva Prayoga; Hermien Nugraheni; Diyah Fatmasari (Poltekkes Kemenkes Semarang, 2020)
Magnetic Resonance Imaging (MRI) examination of the brain at high resolution will be able to detect abnormalities in the brain that are not detected before. The MRI machine is equipped with a very strong magnetic force, therefore metal objects can interfere with the workings of the machine . Some patients, there may be a magnet in the body unnoticed, for example: orthodontic bracket. The purpose of this study was to analyze the effectiveness of sequences to reduce metal artifacts due to the installation of the Orthodontic Bracket. This type of research is a quantitative analytic with a quasi-experimental research design. The research design used was a one group pretest-posttest design to determine the optimization of the application of the Slice Encoding Metal Artifact Correction (SEMAC) and View Angle Tilting (VAT) sequences on Brain MRI with Orthodontic Bracket. The results showed that the SEMAC sequence combined with T2 TSE was able to reduce metal artifacts well. VAT sequences combined with T2 TSE were able to reduce metal artifacts quite well. A more optimal sequence to reduce metal artifacts is T2 TSE SEMAC, where the sequence is able to reveal thin structures that are not visible in the T2 TSE or T2 TSE VAT sequences.